Sources of international law in the legal system of a modern state - Polovchenko, Konstantin A. (Opción, 2019)
The paper presents an analysis of the problem of the relationship between international and domestic sources of law in the legal system of the Republic of Serbia under the 2006 Constitution. The structural-functional and comparative-law methods allowed analyzing the hierarchy of sources of law and the role of the Constitutional Court in ensuring it. The author came to the conclusion that the modern Constitution of Serbia solved the issue of the relationship between international and domestic laws in favor of the monist doctrine, in accordance with which international and domestic laws are two components of the unified legal system.